2015
DOI: 10.1016/j.trd.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Transport energy consumption in mountainous roads. A comparative case study for internal combustion engines and electric vehicles in Andorra

Abstract: This paper analyses transport energy consumption of conventional and electric vehicles in mountainous roads. A standard round trip in Andorra has been modelled in order to characterise vehicle dynamics in hilly regions. Two conventional diesel vehicles and their electric-equivalent models have been simulated and their performances have been compared. Six scenarios have been simulated to study the effects of factors such as orography, traffic congestion and driving style. The European fuel consumption and emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The energy consumption model for an internal combustion engine vehicle is formulated in terms of the work of the tractive force necessary to overcome acceleration resistance, air resistance, gradient resistance, and rolling resistance and is also used for EVs [15,40] and given by:…”
Section: Energy Consumption Estimation Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy consumption model for an internal combustion engine vehicle is formulated in terms of the work of the tractive force necessary to overcome acceleration resistance, air resistance, gradient resistance, and rolling resistance and is also used for EVs [15,40] and given by:…”
Section: Energy Consumption Estimation Modelsmentioning
confidence: 99%
“…η 1 and η 2 are the two parameters of this function, which are estimated in the regression model. The aerodynamic friction loss [15,40] is given by:…”
Section: Average Energy Consumption Estimation Per Unit Distancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in the particular case of Andorra, the high grades of its roads have a major impact on energy consumption. In analysing the gap between fuel economy under the NEDC and under real driving conditions in Andorra, a gap of 39.6% between NEDC consumption and real-road figures (Travesset-Baro et al, 2015) has been shown. In this paper, this value is assumed as an on-road factor, which is applied to all car categories.…”
Section: Specific Energy Consumptionmentioning
confidence: 99%